Advances in Gene-Based Therapies for Leber Congenital Amaurosis: A Review of Clinical Trials - Michael Wiryadana; Talenta Sigalingging (GLOBAL HEALTH SCIENCE GROUP, 2025)
Leber congenital amaurosis (LCA) is characterized by early-onset significant vision loss in infancy. Conventional therapeutic strategies offered limited benefits, thus escalating the focus on research into gene-based therapies. This review aimed to explore the clinical trials focusing on gene-based therapies for LCA. This literature review identified clinical trials on gene-based therapies for LCA registered on ClinicalTrials.gov using the keyword “Leber congenital amaurosis OR LCA,” with no restriction on year of registration. Trials not involving gene therapy were excluded. For each eligible trial, the corresponding National Clinical Trial (NCT) number was used to search the PubMed database for peer-reviewed publications, and grey literature was sourced when no publications were available. Extracted data included patient inclusion criteria, sample size, intervention dosage, safety profiles, adverse events, and efficacy outcomes. Numerous gene-based therapies for LCA have been reported, especially those targeting mutations in RPE65, CEP290, GUCY2D, AIPL1, and LCA5. Adeno-associated virus (AAV)-mediated gene replacement therapies, CRISPR/Cas9 gene editing, and antisense oligonucleotides (AONs) have been reported to deliver promising outcomes for LCA. Luxturna (voretigene neparvovec) has been FDA-approved for RPE65-LCA, while trials on emerging therapies like EDIT-101 and sepofarsen hold therapeutic promise for CEP290-LCA. The review underscores emerging strategies in gene therapy that lay the foundation for tailored, mutation-specific treatments. Several challenges remain in optimizing delivery vectors, preserving long-term efficacy, and minimizing adverse events.